Pengembangan Model Pendidikan Agama Islam dalam Membentuk Karakter Empati pada Generasi Z - Miftakhuddin, Muhammad (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
Z generation lives in the era of high technology. Their life is based on the technology such as depending on the social media. So, this generation has moral degradation, disrespect others and surroundings’ ignorance. Then, Islamic education has a big role to create characteristic of empathy toward this generation. This research is aimed to develop Islamic educational model which is simple, effective and applicable in creating empathy’s characteristic toward Z generation. The method of the research is developmental research. The researcher uses questionnaire, interview and documentation technique to collect data. Then the object of the research is Islamic educational model. Therefore, this research creates Islamic education which covers; purpose, material, source of study, method, media, studying process, evaluation and living practice. The result of individual test, group test and limited-test shows the average score 3.90, 3.93, and 4.00. So that, that result is applicable. However, the effectiveness of test analysis’ result by using SPSS 16 application is gained t value 4.817 and p=0.00 <0.05. So that, the mentioned result shows that this Islamic educational model is effective to create characteristic of empathy toward Z generation.